Profitability in The Automotive and Component Industry - Lydia I. Kumajas; Nikolas F. Wuryaningrat; Herningsih S. Lembong (Asia Pacific Journal of Management and Education (APJME), 2021)
The Covid 19 pandemic caused a slowdown in economic growth, which resulted in decreased production and sales of several industrial sectors. The automotive and components sectors faced the same condition, which impacted their production and sales. Paired sample t-test data analysis choose to analyses tend to measure the effect of Profitability during the pandemic and before the pandemic. The result of this study shows that even the automotive industry predicts having contraction on their Profitability at the pandemic period. However, the decline in sales and production is not always followed by a decline in financial performance, especially Profitability, due to financial management policies and efficiency factors. Hence, he automotive and components sub-sector in this study showed no significant difference in Profitability before the Covid 19 pandemic and during covid 19.